Multiculturalism In Indonesian Civilization (Critical, Tolerant, And Empaty) - Imam Safi’i; Hepi Ikmal (Universitas Yudharta Pasuruan, 2020)
The plurality that exists in Indonesia as something real and must be understood by all the elements in this nation, do not let these differences cause a split in the dynamics of community life. From here, this research will focus on how multicultural travel and conditions exist in Indonesia, and at the same time looking at the factors that make multiculturalism remain in one unity, living in harmony in diversity. This research provides a very encouraging answer that a harmonious life in the Indonesian nation can be realized due to critical attitudes, tolerance and empathy, therefore the attitude that makes this harmony must continue to be carried out by understanding each other so that peace will continue to exist in the life of the Indonesian nation